Influence of multi-impacts on GFRP composites laminates - Amaro, A. M. (2013)
The behaviour of Glass Fibre Reinforced Composites (GFRPs) under single and multi-impact events of the same total energy was analysed. Experimental tests were performed considering circular simple supported plates impacted on its centre. The analyses of the results issuing from load–time, load–displacement and energy–time curves have shown that the sole impact of 3 J is more detrimental for the plate, relative to the other cases of cumulative damage (1 J + 2 J and 1 J + 1 J + 1 J). A fine-tune analysis of damage evolution between subsequent impacts using a numerical procedure including a cohesive mixed-mode damage model was also performed. This analysis permits to verify the evolution of the projected delaminated area as well as the fracture process zone in the vicinity of delaminations. It was verified that a negligible evolution of damage occurs in the case of three consecutive impacts of the same energy. Additionally, it was concluded that the cumulative damage in the case of (1 J + 2 J) is inferior to the one propitiated by the sole impact of maximum energy (3 J).